Translating conduction-electron spin-resonance lines into lorentzian lines - Walmsley, L. [UNESP] (Elsevier, 1996)
The Dysonian line in the limit d < or ∼ δ, where d is the thickness and 6 the skin depth, was fitted to a combination of absorption and dispersion Lorentzian lines. This procedure allows one to determine not only microwave conductivity from the Dysonian line but also the true g value, linewidth, and paramagnetic susceptibility by the measurement of five parameters of the ESR absorption-derivative Dysonian line. ©1990 Academic Press, inc.